Causes of rising failure of the students’ in the subject of English at Secondary Level - Shahzada, Gulap; Ghazi, Safdar Rehman; Khan, Umar Ali (Richtmann Publishing, 2012)
Purpose of this research was to find out causes of rising failure of the students’ in the subject of English at SecondaryLevel. This study was descriptive in nature. All the male secondary schools in district Bannu constituted population of this study.From 50 secondary schools 100 English teachers were randomly selected as a sample of the study. A questionnaire forsecondary school teachers was developed to collect data. To analyze and interpret data, simple percentage was used. Resultsof the study showed that majority of the respondents approved that teacher of English are not qualified and well trained, teachersof English do not teach English in a proper manner, Audio- Visual aids are not used in English class, The course is notcompatible to the present time, teachers of linguistics are not present in our schools, English is given importance in the annualprogress of the students in school. It was recommended that Qualified and well trained teachers may be appointed for English,teachers of English may use modern teaching method instead of traditional methods, Audio visual aids may be used such aslanguage lab, gramophone, English course may be made compatible to the present time, Teachers may be encouraged to getlinguistics knowledge.